Cervical cancer screening among women with comorbidities: evidence from the 2022 Tanzania demographic and health survey - Joshua Okyere; Castro Ayebeng; Abigail Kabukie Dosoo; Kwamena Sekyi Dickson (BMC, 2024)
Abstract Background The aim of this study is to examine cervical cancer screening (CCS) uptake among women living with hypertension and HIV in Tanzania. Methods We used the recently released 2022 Tanzania Demographic and Health Survey. The outcome variable assessed in the study was CCS, whereas chronic morbidities constituted the main explanatory variable. Data analysis was based on observations from 6,298 women aged 30-49 years. Multivariable logistic regression models were used to determine the association between hypertension and HIV status, and CCS uptake. The analyses were computed in STATA 18. Results Out of the 6,298 respondents, only 805 (12.8%) had undergone CCS with higher screening uptake among those living with either one of the disease (28.5%) than among those living with neither hypertension or HIV. The highest proportion was found among those who had ever been diagnosed with hypertension (24.1%) and among women with positive HIV test results (36.7%). There was a significantly higher likelihood of undergoing screening for cervical cancer among women living with at least one of the diseases [AOR = 2.4; 95% CI: 1.4-2.8], compared to those without these conditions. Women diagnosed with hypertension showed increased likelihood of undergoing CCS [AOR = 1.4; 95%CI: 1.1-1.7]. Similarly, women with a positive HIV test result demonstrated higher odds of screening uptake [AOR = 5.2; 95%CI: 4.0-6.7]. Conclusion The study found a positive association between comorbidities and CCS uptake in Tanzanian women. Our findings emphasize the critical importance of ensuring accessibility and adherence to essential screenings for individuals with chronic morbid conditions. Future efforts should focus on strengthening existing integrated services and identifying potential barriers to accessing CCS within these healthcare settings to optimize cervical cancer prevention efforts for individuals with chronic morbidities.